If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-1)=6x-2(x-2)
We move all terms to the left:
4(x-1)-(6x-2(x-2))=0
We multiply parentheses
4x-(6x-2(x-2))-4=0
We calculate terms in parentheses: -(6x-2(x-2)), so:We get rid of parentheses
6x-2(x-2)
We multiply parentheses
6x-2x+4
We add all the numbers together, and all the variables
4x+4
Back to the equation:
-(4x+4)
4x-4x-4-4=0
We add all the numbers together, and all the variables
-8!=0
There is no solution for this equation
| -7z−6=-5z | | t+6(16)+9=14+16+32 | | 25.50=10.75x | | U-5=-4(w-1) | | 1x+9=6x+0 | | 8b-20=12b= | | -y+6=-9+4y | | 25.50x=10.75 | | 9+6y=3y | | x-51=90 | | 6x-9=-4x+11 | | 3+9x+8=x+ | | 1x+9=6x+5 | | 5x*20+7x-8=180 | | |x|-7=2 | | 5x20+7x-8=180 | | 0x+2=9x+5 | | -4x-8=-2x+12= | | 9y=6-18 | | u+16=2u | | 6d-11/2=2d-12/3 | | -(-4g+7)=-2+4g | | (2z-8)^2+55=43 | | 19-3r=7 | | (24x-11)+47=180 | | -17+b÷8=1÷ | | 3c+12=15 | | −7x^2−91x−280=0 | | 2.5d+7.75=4+3.75 | | 4x+20=26+x+24 | | 7+9x+2=16x-5 | | z−-231=314 |